Mechanism for the Operationalization of the Forest Stewardship Council Policy on Conversion - CGIAR Research Program on Forests, Trees and Agroforestry (2021)
Additional innovation as Remedy procedure was adapted for use in new Remedy Framework, which also addressed violations of FSC Policy for Association. Second draft subjected to 3 month international public consultation. Third draft then produced based on consultation inputs.